Uji Aktivitas Antibakteri Senyawa Flavonoid dari Rimpang Temu Kunci (Kaempferia pandurata Roxb.) terhadap Streptococcus mutans - Handayani, Siti; Mursiti, Sri; Wijayati, Nanik (Indonesian Journal of Chemical Science, 2018)
Fingerroot (Kaempferia pandurata Roxb.) is one other from varient traditional medicine plant was many grow in Indonesia. This plant had many compounds of secondary metabolite that used for antibacterial. The other one bacterial causing tooth plaque was tooth and mouth diseases which many alert by Indonesians. The most roling bacterial in causing it is Streptococcus mutans. The study aims to determine isolation flavonoid compound and the activity to inhibit bacterial growth. The compound obtained with isolates the fingerroot using coloumn chromatography was extracted with maseration method. Coloumn chromatography result analized with UV-Vis and FTIR spectrofotometre. Antibacterial activity method is agar difusion using paper disk. The results showed that isolation compound is flavanone, that is 6.7.3â.4â-tetrahidroxy flavanone. Activity showed that flavanone is resistent against Streptococcus mutans and have lower activity than ethanol extract samples amount 1.85 mm.